2019
DOI: 10.1055/s-0039-1678663
|View full text |Cite
|
Sign up to set email alerts
|

Converting the Distinct Heparins Sourced from Bovine or Porcine Mucosa into a Single Anticoagulant Drug

Abstract: Unfractionated heparin (UFH) and their low-molecular-weight derivatives are sourced almost exclusively from porcine mucosa (HPI); however, a worldwide introduction of UFH from bovine mucosa (HBI) has been recommended to reinforce the currently unsteady supply chain of heparin products. Although HBI has different chemical composition and about half of the anticoagulant potency of HPI (∼100 and ∼180 international unit [IU]/mg, respectively), they have been employed as interchangeable UFHs in some countries since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…The anticoagulant activity of UFH is due to the AT/HCII-mediated inactivation of several coagulation system enzymes, especially FIIa, and FXa [37]. Our in vitro assays revealed that PNH exerts a negligible anticoagulant activity, mostly mediated by HCII.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The anticoagulant activity of UFH is due to the AT/HCII-mediated inactivation of several coagulation system enzymes, especially FIIa, and FXa [37]. Our in vitro assays revealed that PNH exerts a negligible anticoagulant activity, mostly mediated by HCII.…”
Section: Discussionmentioning
confidence: 73%
“…Our in vitro assays revealed that PNH exerts a negligible anticoagulant activity, mostly mediated by HCII. This reduced AT-mediated anticoagulant potency may occur due to the absence of the specific pentasaccharide sequence present in UFH, which promotes the conformational change responsible for potentiating AT [37,38]. Despite presenting mostly a serpin-independent anticoagulant activity, the FucCS from H. grisea also activates HCII; nevertheless, its activity (~50 IU/mg) is far higher than that obtained with PNH [15].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, our research group demonstrated that pharmaceutical HBI is actually composed of a mixture of two types of heparin chains bearing different chemical compositions and anticoagulant activities, which in turn can be separated through a single ion-exchange chromatography step (Fig. 1), named as Highanticoagulant Bovine Heparin (HABH) and Low-anticoagulant Bovine Heparin (LABH) 18,19 . While HABH has chemical composition (enriched in N,6-disulfated αglucosamine) and anticoagulant activity (~200 IU/mg) similar to HPI, LABH has diminished potency (~25 IU/mg) due to the preponderance of disaccharides containing N-sulfated but not 6-sulfated α-glucosamine (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1). Different from HBI, HPI and pharmaceutical preparations sourced from bovine lung contain diminished amounts of low-anticoagulant heparin chains such as those component of LABH 18 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the current article by Tovar et al, 4 a straightforward application of bovine heparin fractionation with anion exchange chromatography to produce a heparin with similar chemical composition, potency and safety profile to porcine heparin is demonstrated. If such a porcine-like heparin product could be made commercially from a bovine source and obtain approval from regulators, a single heparin drug from different animal sources with different geographical distribution with consistent quality could improve supply chain stability for this important drug.…”
mentioning
confidence: 99%